2018
DOI: 10.1159/000495155
|View full text |Cite
|
Sign up to set email alerts
|

Increased KIF15 Expression Predicts a Poor Prognosis in Patients with Lung Adenocarcinoma

Abstract: Background/Aims: Lung cancer is the leading cause of cancer-related deaths worldwide. The outcome of patients with non-small cell lung cancer remains poor; the 5-year survival rate for stage IV non-small cell lung cancer is only 1.0%. KIF15 is a tetrameric kinesin spindle motor that has been investigated for its regulation of mitosis. While the roles of kinesin motor proteins in the regulation of mitosis and their potentials as therapeutic targets in pancreatic cancer have been described previously, the role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 41 publications
2
29
0
Order By: Relevance
“…Up to date, over 600 members of the kinesin superfamily have been identified in addition to more than 45 members of mammals [11]. Increasing studies [8,[12][13][14][15][16] have shown that KIFs is related to the initiation and progression of breast cancer, lung cancer, and pancreatic cancer. Moreover, KIFs may be therapeutic targets for non-small cell lung cancer (NSCLC) [17].…”
Section: Introductionmentioning
confidence: 99%
“…Up to date, over 600 members of the kinesin superfamily have been identified in addition to more than 45 members of mammals [11]. Increasing studies [8,[12][13][14][15][16] have shown that KIFs is related to the initiation and progression of breast cancer, lung cancer, and pancreatic cancer. Moreover, KIFs may be therapeutic targets for non-small cell lung cancer (NSCLC) [17].…”
Section: Introductionmentioning
confidence: 99%
“…KIF15 ablation inhibits endocrine therapy-resistant breast cancer [23]. Additionally, KIF15 is high-expressed in lung cancer and involved in cancer development by regulating the cell cycle [22]. KIF15 also promotes the proliferation of pancreatic cancer via MEK-ERK pathway [21].…”
Section: Discussionmentioning
confidence: 99%
“…KIF15 seems to be a good target for cancer as it plays a key role during cell mitosis. Actually, KIF15 has also been demonstrated to be involved in the growth of various types of tumors, such as pancreatic cancer, lung cancer, and breast cancer [21][22][23]. However, the possible functions of KIF15 in HCC tumorigenesis and the relationship with prognosis are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…This redundancy between Kif15 and Eg5 is of interest as a potential factor in the disappointing ineffectiveness thus far of Eg5 inhibitors as cancer therapeutics (Tanenbaum et al , 2009;Rath and Kozielski, 2012;Milic et al , 2018;Dumas et al , 2019) . It is particularly notable since Kif15 overexpression results in lagging chromosomes (Malaby et al , 2019) , and is upregulated in a number of cancers (Ma et al , 2014;Wang et al , 2017;Qiao et al , 2018;Yu et al , 2019;Zhao et al , 2019;Sun et al , 2020;Terribas et al , 2020) . Under normal circumstances, however, Kif15 localizes predominantly to k-fiber microtubules.…”
Section: Introductionmentioning
confidence: 99%
“…This redundancy between Kif15 and Eg5 is of particular interest as a potential factor in the disappointing ineffectiveness thus far of Eg5 inhibitors as cancer therapeutics (Tanenbaum et al 2009;Milic et al 2018;Dumas et al 2019;Rath and Kozielski 2012) . Furthermore, Kif15 upregulation is found in a number of cancer types and can result in rapid cancer cell proliferation (Wang et al 2017;Zhao et al 2019;Yu et al 2019;Qiao et al 2018;Sun et al 2020;Terribas et al 2020;Ma et al 2014) . Under normal circumstances, however, Kif15 localizes predominantly to k-fiber microtubules.…”
Section: Introductionmentioning
confidence: 99%